Health Professionals' Practices and Attitudes About Miscarriage. Issue 1 (January 2016) - Engel, Joyce; Rempel, Lynn
Abstract: Purpose: The purposes of the study were to explore relationships between attitudes, beliefs, and practices of healthcare professionals caring for women and families experiencing miscarriage and to identify gaps and barriers in follow-up services and supports for these women and families. Study Design and Methods: A survey about beliefs, attitudes, and practices regarding women and families experiencing miscarriage and barriers to care was conducted electronically and through distribution in three emergency departments (EDs). There were 174 participants; physicians ( n = 50), RNs ( n = 63), midwives ( n = 38), nurse practitioners ( n = 9), and others ( n = 4). Results: Participants believed that miscarriage can have high impact on women and families. They provided information to patients about miscarriage and its present and future implications. The most important predictor for mobilization of support by healthcare professionals was confidence. Nurses in EDs reported the least amount of confidence and knowledge to provide women and families with support. Availability and awareness of specific services by professionals and health system issues were identified as barriers to care. Clinical Implications: Education of healthcare professionals, particularly of RNs in EDs, is important to address misconceptions about miscarriage, increase confidence in providing support, and promote effective care. Women and families experiencing miscarriage need privacy and timeliness in care. Interventions such as funded midwifery loss care or a routine telephone follow-up call could improve access to care and help healthcare professionals ensure that families obtain the type and amount of support that they need. Abstract : Many women come to the emergency department when they are having a miscarriage; however, nurses and physicians in the emergency department do not always know how to best help women through this devastating life event.